2006
DOI: 10.1039/b516552k
|View full text |Cite
|
Sign up to set email alerts
|

Highly enantioselective DNA-based catalysis

Abstract: A new approach to DNA-based asymmetric catalysis is presented, which gives rise to very high enantioselectivities (up to 99% ee) in the copper catalyzed Diels-Alder reaction in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
132
1
6

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 199 publications
(142 citation statements)
references
References 26 publications
3
132
1
6
Order By: Relevance
“…With the second generation of ligands (Scheme 17 b), which do not contain a separate DNA binding moiety, up to 99 % ee was obtained in the case of 4,4'-dimethyl-bipyridine (41). [42] The corresponding Cu 2 + complex, however, has only a moderate DNA-binding affinity and displays no sequence selectivity in binding. Moreover, the DNA binding www.chemeurj.org mode is not well defined.…”
Section: Helical Polymers That Do Not Contain Chiral Side Chainsmentioning
confidence: 99%
“…With the second generation of ligands (Scheme 17 b), which do not contain a separate DNA binding moiety, up to 99 % ee was obtained in the case of 4,4'-dimethyl-bipyridine (41). [42] The corresponding Cu 2 + complex, however, has only a moderate DNA-binding affinity and displays no sequence selectivity in binding. Moreover, the DNA binding www.chemeurj.org mode is not well defined.…”
Section: Helical Polymers That Do Not Contain Chiral Side Chainsmentioning
confidence: 99%
“…The NMR spectra of selective compounds were recorded in Bruker AV 400 spectrometer operating at 400 MHz for 1 H NMR spectra and 100 MHz for 13 C NMR spectra in CDCl 3 solvent using TMS as internal standard. Electron impact and chemical ionization mode FAB + mass spectra were recorded with a SHIMADZU spectrometer.…”
Section: Generalmentioning
confidence: 99%
“…Numerous catalysts including Lewis acids [4], Bronsted acids [4,10], asymmetric catalyst with helical polymers [11], Cu 2+ ion-mediated nanotubes [12], DNA and Micellar based catalysts [7,[13][14][15][16] have been used for this [4+2] cycloaddition Diels-Alder reaction of cyclopentadiene(diene) and E-chalcones(dienophiles).…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] Furthermore, a DNAzyme capable of enantioselection of an RNA substrate [24] and an enantioselective Diels-Alderase RNAzyme have been reported. [25] In our approach to DNA-based enantioselective catalysis, [26][27][28] we have demonstrated that the chirality of DNA can be transferred directly to a metal-catalyzed reaction. The design involves the modular assembly of a DNA-based catalyst from natural duplex DNA, usually salmon testes DNA (st-DNA), and a copper complex of an achiral ligand that can bind DNA in a noncovalent fashion.…”
Section: Introductionmentioning
confidence: 99%